A Case of Cephalic Tetanus in a Developed Country. (January 2013) - Fusetti, S.; Ghirotto, C.; Ferronato, G.
Tetanus is a potentially life-threatening infection that results from contamination of skin wound by Clostridium Tetani spores. Although, it remains an important health problem in developing countries without strict national immunization programs, this condition is rare in the developed world. The most frequent presenting symptoms are trismus and dysphagia, due to the spasmodic contraction of the masticatory muscles. Then the disease usually diffuses with a descending pattern inducing a generalized contraction of the agonist and antagonistic muscles, which characterize a tetanic spasm. Mortality usually results from respiratory failure, cardiovascular collapse, or autonomic dysfunctions. Treatment usually requires the prompt admission to the intensive care unit to avoid the development of potential life-threatening complications. We report the case of a 78-year-old farmer, who was referred to us with progressive onset of lock-jaw and muscular stiffness of the facial region, that had occurred after he had scratched himself with a rose. The recognition of the presenting signs of cephalic tetanus allowed the prompt management of the infection. However, because of the rarity of this condition, the clinicians may be unfamiliar with the clinical presentation, and be unsuspecting of the diagnosis.